Adapted Primary Literature in Authentic Science: Students’ Perception - Toni Hidayat; Nuryani Rustaman; Parsaoran Siahaan (Journal of Science Learning, 2021)
Science textbooks only present scientific facts that cause the textbooks to seem not to promote scientific reasoning. Science learning also becomes not in line with the nature of Science. Then, Science learning requires applying authentic Science as an approach. Adapted Primary Literature (APL) is assumed to be able to achieve this objective. Therefore, this study aims to examine how APL is a source of Science learning in actualizing authentic Science. This research using a quasi-experimental method, 81 students from two 7th grade groups were involved as participants. One group analyzed APL using a jigsaw, another using a Numbered Heads Together (NHT). A perception questionnaire of APL was given. Quantitative analysis was only performed on data from 44 students due to other students’ participation that is lacked by a pandemic. The result showed both classes possess a high perception of APL. A mean difference test also showed that there were no differences in perception between the two classes. These indicated that analyzing APL was perceived as an authentic Science. Science teachers can utilize APL as an alternative way to actualize authentic Science with a relatively more straightforward model, strategy, and method than commonly applied.